PENGEMBANGAN SISTEM PENENTUAN MAHASISWA BERPRESTASI DENGAN PENDEKATAN SIMPLE ADDITIVE WEIGHTING MENGGUNAKAN PEMBOBOTAN ENTROPY PADA UNIVERSITAS MUHAMMADIYAH METRO - mahdaleni; Febriyanto; Marhaban Sigalingging; Kuncoro Budi Riyanto (SIMPLEX: Journal of Economic Management, 2026)
This study aims to find the criteria for decision making for determining outstanding students and how to develop a system for determining outstanding students with the Simple Additive Weighting approach using entropy weighting at Muhammadiyah Metro University. This study uses a survey method with a quantitative descriptive approach. Data collected were 100 student respondents from 7 faculties at Muhammadiyah Metro University. Data analysis with the Simple Additive Weighting approach steps using entropy weighting. The results of the study show that there are several types of criteria used, namely: IPK, number of attendance, involvement in scientific activities, english language competence, sports and arts achievements, and experience in organizations. The Simple Additive Weighting method with entropy weighting is able to provide objective and accurate ranking results as well as mathematical and scientific, so that decisions are fairer and more measurable. This study provides suggestions for the need to add more comprehensive criteria such as community service, entrepreneurial activities, and international recognition that will enrich the assessment and reflect the quality of students more comprehensively. Keywords: Outstanding students, simple additive weighting, entropy weighting.